User Interface/User Experience Academic Information System (SIAM) Design Using the Lean User Experience (Lean UX) Method at WR. Supratman University - Pungki Yoga Budistria; Sulistiowati .; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2020)
SIAM is a web-based academic information system application at WR Supratman University in Surabaya with the aim to provide information about students' academics. From the results of a review of the SIAM similarweb application, there were fewer visitors due to the unattractive and less responsive user interface / user experience on the smartphone display, whereas the number of users through smartphones reached 78% more than users accessing via a PC. Besides that, from the results of the questionnaire to 30 users, it is known that the appearance of SIAM when accessed via smartphone 84% of students stated that the application still looks less attractive and still does not look neat. The solution of this problem is to design a user interface / user experience that is specific to smartphone devices using the Lean UX method, consisting of 4 stages namely Declare Assumptions, Creat an MVP, Run an Experiment, Feedback and Research. The test was conducted on 30 students of WR Supratman University. From the First iteration it is known that the success rate of the prototype reaches 85%, while the second iteration reaches 92% which indicates an increase in the user interface / user experience from before. This shows that the prototype produced is good enough in terms of user interface / user experience so that the prototype can be easily used on a smartphone display